Psychosocial factors that influence students of Modern Languages Major: Specialty French and English to change their Major to the B.A. in English oriented to teaching at the FLD at UES - Fránco Alfáro, Leticia Jeannette; Mejía Déras, María Guadalupe; Elías Erroa, Alex Antonio (2024)
This quantitative research project is oriented to determine to what extent psychosocial factors influence students of Modern Languages Major (MLM): Specialty French and English to change to the B. A. in English Oriented to Teaching. The participants of this study were students who had changed from MLM to the B.A in English Oriented to Teaching at the Foreign Language Department at the University of El Salvador. To identify students who could fit in this study, a first questionnaire was designed. In order to obtain the appropriate data, a second questionnaire was addressed to the students who constituted the sample population. Throughout the investigation, some possible factors influencing major changings were found. These ones included aptitude for the subject, prior knowledge, and academic environment, among others. The results suggest that students’ selfperceptions affect negatively their academic performance. Therefore, it strongly influences their aptitude for the subject. Also, the findings show that the lack of prior or previous knowledge of French influences strongly on this matter. Furthermore, the generated academic environment is considered as another factor for students to make a change in their majors. Finally, the results present an association between students’ weaknesses that influence their decision of changing major. Of course, there is a very close relationship among those factors. This work also contains important recommendations with the purpose of avoiding the tendency of changing from MLM.